Gestão de resíduos sólidos no município de Tibagi - PR: desempenho da coleta seletiva - Zoner, Taynara Assano [UNESP]; Bongiovanni, Solange [UNESP] (My University, 2012)
The objective of this study was to analyze the performance of solid waste management in the municipality of Tibagi, Paraná, a city with approximately 20000 inhabitants, which implemented the selective collection program called Recycle Tibagi. The analysis was based on descriptive statistical techniques, considering the three types of waste (tailings, organic and recyclable), and per capita generation of garbage upward trend in the coming years, based on the method of Winter (Triple Exponential Damping), using data recorded by the Department of the Environment and the Association of Recyclable Materials from Tibagi - ACAMARTI. Efficient selective collection from a structured environmental education program with constant training conducted with the scavengers, possible to obtain important data in sorting and marketing of recyclable materials, saving raw materials, water and energy, as well as relevant indicators social inclusion and employment generation and income. The project involves several areas of municipal management and arouses curiosity and interest in several areas: social, financial, environmental and administrative. It's a way to encourage new projects and public bodies, highlighting the importance of recycling and proper disposal of solid waste.

O objetivo deste trabalho foi analisar o desempenho do gerenciamento de resíduos sólidos do município de Tibagi, Paraná, cidade com aproximadamente 20 mil habitantes, que implantou o programa de coleta seletiva denominado Recicla Tibagi. A análise foi baseada em técnicas estatísticas descritivas, considerando os três tipos de resíduos (rejeito, orgânico e reciclável), geração per capita e tendência do aumento do lixo nos próximos anos, baseada no método de Winter (Amortecimento Exponencial Triplo), através de dados registrados pela Secretaria do Meio Ambiente e a Associação de Catadores de Materiais Recicláveis de Tibagi - ACAMARTI. A eficiente coleta seletiva a partir de um estruturado programa de educação ambiental com constantes treinamentos realizados com os catadores, possibilita a obtenção de dados importantes na triagem e comercialização dos materiais recicláveis, gerando economia de matérias-primas, água e energia, além de relevantes indicadores de inclusão social e geração de emprego e renda. O projeto envolve diversas áreas da gestão municipal e desperta curiosidade e interesse de diversas áreas: social, financeira, ambiental e administrativa. É uma forma de incentivar novos projetos aos órgãos públicos e, ressaltar a importância da reciclagem e destinação adequada dos resíduos sólidos urbanos.
Keywords: Tibagi; Management of municipal solid waste; Selective collection; Tibagi; Gestão de resíduos sólidos urbanos; Coleta seletiva